Happy Easter, Mouse! - Numeroff, Laura Joffe; Bond, Felicia (New York : HarperCollins/ Balzer+Bray, 2010)
Join Mouse from "If You Give a Mouse a Cookie" as he tries to figure out who's leaving Easter eggs all over his house.
"An if you give...book"--cover.
On board pages.
Keywords: Mice -- Juvenile fiction; Easter stories; Eggs -- Juvenile fiction; Counting -- Juvenile fiction; Board books